Predicting Burn Patient Mortality: A Comparative Analysis of the BOBI and R-Baux Scoring Systems - Abda Arif; Ruli Robi Ferli; Theodorus (Sriwijaya Journal of Surgery, 2025)
Introduction: Burns represents a significant global health challenge, causing considerable morbidity and mortality. Accurate prognostication is crucial for optimal burn care management. This study compared the accuracy of the BOBI and R-Baux scores in predicting mortality among burn patients. Methods: This retrospective study analyzed data from 46 burn patients treated at Dr. Mohammad Hoesin General Hospital Palembang. Patient demographics, burn characteristics, and mortality outcomes were recorded. BOBI and R-Baux scores were calculated for each patient. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and Youden Index were determined for both scores. Agreement between the scores was assessed using the Kappa statistic. Statistical analysis was performed using SPSS v25. Results: The majority of patients were male (76.1%) and under 50 years old (84.8%). Fire burns (63%) and superficial-mid dermal injuries (32.6%) were most prevalent. The BOBI score demonstrated fair accuracy (sensitivity: 84.6%, specificity: 63.6%, PPV: 0.478, NPV: 0.913, Youden Index: 0.480). The R-Baux score showed lower sensitivity (76.9%) but higher specificity (78.8%) (PPV: 0.588, NPV: 0.896, Youden Index: 0.560). The Kappa test indicated good agreement between the two scores (κ = 0.783, p = 0.000). Conclusion: Both BOBI and R-Baux scores can be used to predict mortality in burn patients. The BOBI score demonstrated higher sensitivity, while the R-Baux score exhibited higher specificity. The choice of scoring system may depend on the specific clinical context and the relative importance of sensitivity and specificity.